Education as a homogenizing engine in indigenous cultures: case study of Aymara children in Northern Chile - Victoria Rivera; Abraham Paulsen (Springer, 2023)
Abstract Chile is a multi-ethnic Republic; a situation which contradicts itself when one looks at the relationship between the State and its ethnic groups, such as the Aymara in the North. One example of this is the implementation of a state-centric educational model which seems to be homogenizing. Taking a Children's Geographies approach, the following work will analyze the specific types of relationships in educational institutions located in the Arica & Parinacota Region, between children from Aymara communities, the State, and adults. Through different qualitative investigative techniques, such as content analysis of drawings made by Aymara children, interviews made with teachers, and participant observation at schools, it seemed that the educational process that the Aymara children experience does not take their culture into consideration, which sets them apart from their parents' and community's identity. This study also uses the lens of Children's Geographies to identify some landmarks in their spatial worldview transformation and their spatiality. Taking everything into account, conclusions are stated on how the normative educational model shapes uprooted children.